Identifikasi Penggunaan Lahan Menggunakan Citra Resolusi Tinggi di Titik Nol Kawasan Ekonomi Khusus Mandalika - Zuhdiyah Matienatul Iemaaniah; Nur Asri Shakila; Mukminah; Abdul Majid Azzuandi (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2023)
The Mandalika Special Economic Zone (KEK) is located in Central Lombok, directly bordered by the Indian Ocean to the south. This area has been designated as an essential zone to support tourism. One of the landmarks in this area is the Mandalika Circuit, which has various impacts on different sectors, including land use. The current land use is part of the region's development and is aimed at supporting this special zone. The purpose of this research is to identify the land use in the area around the central point of the Mandalika Circuit. The study was conducted in one of the supporting villages within the Mandalika Special Economic Zone (KEK), namely Desa Kuta, which is situated at the central point of the circuit. The research methodology used spatial analysis with ArcGIS 10.5, utilizing high-resolution satellite images from Google Earth. The findings revealed 12 types of land use in the area: shrubland, terraced fields, plantations, the circuit itself, water bodies, circuit facilities, places for activities and settlements, roads, paddy fields, industries, open land, and grassland. The most extensive land use was shrubland, covering 57% of the total area of 2,366 hectares, while the lowest land use was industry occupying only 0,4 % of the total area.